Social computing and virtual communities - Zaphiris, Panayiotis; Chee Siang, Ang (My University, 2010)
The advance of computer technology, particularly the development of the Internet has impacted virtually every aspect of society. Unsurprisingly research and development in the area of social computing, as well as virtual communities, has emerged and is increasingly gaining importance. This book brings together contributions from international experts from various fields and strives to explore the social use of computers. Social Computing and Virtual Communities not only improves productivity and learning outcomes via collaborative work and learning, but also augment human relationships, by providing various means of communication that nullify the geographical barriers existing among us. In addition, it transforms the platform of digital entertainment, infusing a social dimension into the already popular internet use. We also witness the formation of persistent and long term communities in the virtual setting, where people congregate to socialise, make friends, give support, etc. Virtual communities continue to grow in term of their size, the nature of use, and the technological aspects, such as the emergence of 3D virtual environments. Due to the escalating use of computers to mediate various social aspects of human activity, some conceptual frameworks have been developed to understand computer-mediated social activities. It is commonly agreed that researching, designing and evaluating virtual communities requires a multi-disciplinary approach that goes beyond methods used for designing and evaluating other interactive systems. Furthermore, it is also crucial to research these issues through naturalistic approaches, in which users’ activity is investigated within its context. Therefore, this book aims at presenting the topic of social computing and virtual communities, from the user’s perspective in various domains of use, through a multi-disciplinary lens. One of the most important characteristics of the interent is the opportunities it offers for human-human communication through computer networks. As Metcalfe (1992) points out, communication is the internet’s most important asset. E-mail is just one of the many modes of communication that can occur through the use of computers. Jones (1995) points out that through communication services, like the Internet, Usenet and bulletin boards, online communication has for many people supplanted the postal service, telephone and even the fax machine. All these applications where the computer is used to mediate communication are called Computer-Mediated Communication (CMC). Studies of CMC view this process from different interdisciplinary theoretical perspectives (social, cognitive/psychological, linguistic, cultural, technical, political) and often draw from fields such diverse as human communication, rhetoric and composition, media studies, human-computer interaction, journalism, telecommunications, computer science, technical communication and information studies. Online communities emerge through the use of CMC applications. The term online community is multidisciplinary in nature, means different things to different people, and is slippery to define (Preece, 2000). Rheingold’s definition of CMC is: “[online] communities are social aggregations that emerge from the Net when enough people carry on those public discussions long enough, with sufficient human feeling, to form webs of personal relationships in cyberspace” (Rheingold, 1993, pp.5). Online communities are also often referred to as cyber societies, cyber communities, web groups, virtual communities, web communities, virtual social networks and e-communities among several others. The cyberspace is the new frontier in social relationships, and people are using the internet to make friends, colleagues, lovers, as well as enemies (Suler, 2004). As Korzeny pointed out, even as early as 1978, online communities are formed around interests and not physical proximity (Korzeny, 1978). In general, what brings people together in an online community is common interests such as hobbies, ethnicity, education, beliefs. As Wallace (1999) points out, meeting in online communities eliminates prejudging based on someone’s appearance, and thus people with similar attitudes and ideas are attracted to each other. These issues are addressed in this book through a collection of chapters contributed by the leading experts in these areas. The book is divided into three sections: A: theories and methods; B: Application areas; C: Types of online social environments.
Keywords: Human-computer interaction; Internet--Social aspects; Computer networks--Social aspects